Rational Design of Polypeptide‐Based Block Copolymer for Nonviral Gene Delivery. Issue 36 (21st December 2017) - Kalinova, Radostina; Doumanov, Jordan A.; Mladenova, Kirilka; Janevska, Dushica; Georgieva, Milena; Miloshev, George; Topouzova‐Hristova, Tanya; Dimitrov, Ivaylo
Abstract: The present work describes the development, characterization, and in vitro evaluation of novel poly(L‐lysine)‐based polyplexes as nonviral gene delivery systems. Initially, a well‐defined hybrid block copolymer comprising poly(ethylene glycol) methacrylate) (POEGMA) and poly(L‐lysine) (PLL) blocks was successfully synthesized and characterized. The hybrid copolymer shows high ability to condense DNA into stable polyplexes in aqueous media with sizes of approx. 100 nm. The nanoplexes were evaluated for cellular toxicity in A549 alveolar and HepG2 (hepatocarcinoma) cell lines. The nanoparticles cell internalization and transfection ability were assessed in HepG2 cells. The initial experiments showed that DNA was successfully transfected into the nucleus of human liver cancer cells and expressed enhanced green fluorescent protein (EGFP) gene with green fluorescence emission. These results revealed that the newly synthesized POEGMA‐b‐PLL diblock copolymer might be very attractive candidate as a nonviral gene delivery vector. Abstract : A novel, rationally designed polypeptide‐based block copolymer (POEGMA‐b‐PLL) is prepared by the combination of ring‐opening polymerization and atom transfer radical polymerization. The POEGMA‐b‐PLL with short oligo(oxyethylene) side chains and biodegradable poly(L‐lysine) block forms colloidally stable and nano‐sized polyplexes with plasmid DNA. The estimated in vitro transfection efficiency suggests that the hybrid block copolymer is a promising candidate for efficient nonviral gene delivery vehicle.